[English original] The evolution of Nordic walking research: a bibliometric analysis - González-Devesa, Daniel (2026)
INTRODUCTION: Nordic Walking has expanded from a sport-specific method to a widely used physical activity and therapeutic strategy, generating a rapidly growing body of literature. PURPOSE: This study aimed to conduct a comprehensive bibliometric analysis of Nordic Walking research from 1996 to 2024. METHODOLOGY: A bibliometric analysis was performed using Scopus. Peer-reviewed journal articles and reviews published between 1996 and 2024 were analyzed. Performance indicators and science-mapping analyses were conducted using Biblioshiny. A total of 331 documents were analysed. RESULTS: The field showed consistent growth, with an annual growth rate of 12.18%, and 39.27% of publications occurring in the last five years (2020–2024). Poland was the leading country in research output (20.8% of publications), followed by Italy (11.6%) and Spain (6.4%). Co-occurrence network analysis revealed three main research clusters centered on physiology, human walking, and exercise therapy. Topic trend analysis identified “Nordic walking,” “physical activity,” “exercise,” and “walking” as dominant themes. International collaboration networks showed strong links among European countries, particularly Italy and Poland. CONCLUSION: This study provides insights into the evolution and current state of Nordic Walking research, highlighting its growing relevance in health and exercise science and supporting future agenda setting and targeted international collaboration.